Parametric analysis of composite sinusoidal specimens under quasi-static crushing. (4th June 2018) - Mou, H. L.; Su, X.; Xie, J.; Feng, Z. Y.
ABSTRACT: This paper aims to build the finite element model of the composite sinusoidal specimens and to carry out the parametric analysis. In this paper, the damage behaviour and the energy-absorbing results of composite sinusoidal specimens have been studied by quasi-static crushing experiments. The failure mechanisms of specimens under quasi-static crushing is further analysed. A numerical simulation has been performed by using the finite element model code LS-DYNA. The numerical results, in terms of load -displacement data, have been compared against experimental data, and good agreement has been found. Moreover, a sensitivity study has been carried out by varying material properties in order to assess their influence on the numerical results, and the material parameter selection scheme is optimised based on the constructed corresponding response surfaces. The results show that the response surface model has passed the test of goodness of fit, and the optimisation method can effectively assist the finite element modelling, and greatly decrease the numbers of trial and error.